2021
DOI: 10.1001/jamacardio.2021.3187
|View full text |Cite
|
Sign up to set email alerts
|

Associations of High-Sensitivity Troponin and Natriuretic Peptide Levels With Outcomes After Intensive Blood Pressure Lowering

Abstract: IMPORTANCE Elevated high-sensitivity cardiac troponin T (hscTnT) and N-terminal pro-B-type natriuretic peptide (NTproBNP) levels are associated with risk of heart failure (HF) and mortality among individuals in the general population. However, it is unknown if this risk is modifiable.OBJECTIVE To test the hypothesis that elevated hscTnT and NTproBNP levels would identify individuals with the greatest risk for mortality and HF and the largest benefit associated with intensive systolic blood pressure (SBP) lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…For example, the 4‐year absolute risk reduction of randomization to the intensive‐treatment group versus standard‐treatment group for all‐cause mortality among individuals without elevated hs‐cTnT and NT‐proBNP was 0.97%, whereas the 4‐year absolute risk reduction was 7.00% among individuals with both biomarkers elevated. 23 We speculate that participants with high cardiac biomarker levels have substantial multimorbidity at baseline that predisposes them to SAEs regardless of their lower achieved BP and use of additional antihypertensive medications following randomization to the intensive‐treatment group. These findings suggest that combined elevations in hs‐cTnT and NT‐proBNP indicate a high SAE risk, but also identify a subset with substantial absolute benefit from intensive BP lowering and no excess risk of harms compared with standard BP lowering.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, the 4‐year absolute risk reduction of randomization to the intensive‐treatment group versus standard‐treatment group for all‐cause mortality among individuals without elevated hs‐cTnT and NT‐proBNP was 0.97%, whereas the 4‐year absolute risk reduction was 7.00% among individuals with both biomarkers elevated. 23 We speculate that participants with high cardiac biomarker levels have substantial multimorbidity at baseline that predisposes them to SAEs regardless of their lower achieved BP and use of additional antihypertensive medications following randomization to the intensive‐treatment group. These findings suggest that combined elevations in hs‐cTnT and NT‐proBNP indicate a high SAE risk, but also identify a subset with substantial absolute benefit from intensive BP lowering and no excess risk of harms compared with standard BP lowering.…”
Section: Discussionmentioning
confidence: 97%
“…Both hs‐cTnT and NT‐proBNP were measured from freshly thawed serum samples using an electrochemiluminescence immunoassay on the Roche Cobas 6000 platform (Roche Diagnostics, Indianapolis, IN) as previously described. 23 The hs‐cTnT assay (5th Generation) has an imprecision of 3.4% at 28.3 ng/L and 2.3% at 2076 ng/L, with a lower limit of quantitation of 6 ng/L. The NT‐proBNP assay has an imprecision of 2.9% at 140.3 pg/mL and 2.7% at 4563 pg/mL, with a lower limit of detection of 5 pg/mL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPRINT study, designed to assess the correlation of a reduction in CV risk with a drastic drop in blood pressure, identified that patients with the highest hs-cTnT values are associated with a higher mortality, and that blood pressure lowering treatment reduces most of the risk in these patients ( 74 ).…”
Section: Troponinsmentioning
confidence: 99%
“…NT-proBNP and hsTnT were measured from stored specimens collected at enrollment (using the Roche COBAS 6000 platform). 7 We determined the proportion of SPRINT participants who were above the 95th and 99th percentile thresholds developed in CRIC, overall and across strata by eGFR category. 5 In secondary analyses, we described these proportions across strata of sex, race, and age.…”
mentioning
confidence: 99%